GIS-BASED ANALYSIS FOR ASSESSING LANDSLIDE AND DROUGHT HAZARD IN THE CORRIDOR OF MT. MERAPI AND MT. MERBABU NATIONAL PARK, INDONESIA - Hero Marhaento (Department of Urban and Regional Planning, Diponegoro University, 2016)
A corridor is an area located between two or more protected areas that are important to support the sustainability of the protected areas. This study is aimed at assessing landslide and drought hazard in the corridor area between Mt. Merapi National Park (MMNP) and Mt. Merbabu National Park (MMbNP) as a part of the corridor management strategy. The corridor area of MMNP and MMbNP comprises four sub-districts in Central Java Province, namely, Sawangan, Selo, Ampel, and Cepogo. A spatial analysis of ArcGIS 10.1 software was used to assess landslide hazard map and the Thornthwaite & Mather Water Balance approach was used to assess drought hazard map. The results have shown that three villages in Cepogo Sub-district and all villages in Selo Sub-district are highly prone to landslide hazard. Furthermore, two villages in Cepogo Sub-district and four villages in Selo Sub-district are prone to drought hazard. This study suggests that these villages should initiate a program called conservation village model based on disaster mitigation for mitigating future landslide and drought disasters.